2013
DOI: 10.2298/pan1301103b
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Tunisian trade banks: Study by the stochastic frontier approach

Abstract: In this paper, we propose to evaluate the scores of productive efficiency of 20 Tunisian commercial banks throughout the period 1990-2009. The local banking landscape was marked, during the studied period, by significant changes following the adoption, by the Tunisian government, of various measures of financial liberalization. In order to study the levels of efficiency cost realized by the Tunisian commercial banks, we propose a parametric method, named the Stochastic Frontier Approach “SFA”, on the one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
3
2
Order By: Relevance
“…Hence, our results provide additional evidence of the positive relationship between ROA and technical efficiency that was found by most of the earlier studies (Saha et al 2015;Tadesse 2017;Banna et al 2019). It is, however, partially in line with the findings of Bannour and Labidi (2013). When bank managers can alter both inputs and outputs, ROA becomes insignificant in explaining technical efficiency.…”
Section: Table 5 Comparison Of Average Original and Bias-corrected Technical Efficiency Of Banks By Type Of Ownership Before And After Thsupporting
confidence: 90%
See 2 more Smart Citations
“…Hence, our results provide additional evidence of the positive relationship between ROA and technical efficiency that was found by most of the earlier studies (Saha et al 2015;Tadesse 2017;Banna et al 2019). It is, however, partially in line with the findings of Bannour and Labidi (2013). When bank managers can alter both inputs and outputs, ROA becomes insignificant in explaining technical efficiency.…”
Section: Table 5 Comparison Of Average Original and Bias-corrected Technical Efficiency Of Banks By Type Of Ownership Before And After Thsupporting
confidence: 90%
“…LDR was found to be significant and positively related to technical efficiency with limited effect in a few bootstrap regressions. Hence, this result is weakly in line with Ben Naceur et al (2011) and contradicts the findings of Bannour and Labidi (2013) who found the LDR to be negatively related to technical efficiency. In particular, our results indicate that a higher liquidity risk may render some Tunisian banks more technically efficient by expanding output despite the risk of incurring higher banking operating costs.…”
Section: Table 5 Comparison Of Average Original and Bias-corrected Technical Efficiency Of Banks By Type Of Ownership Before And After Thcontrasting
confidence: 89%
See 1 more Smart Citation
“…As the examples of using technical efficiency in the field of banking activity analysis we can mention the works of Ali Ataullah, Tony Cockerill and Hang Le [11], Iftekhar Hasan and Katherin Marton [12], Fotios Pasiouras [13], Bannour Boutheina and Labidi Moez [14] and many others. The expediency of using technical efficiency for the analysis of economic processes of banks functioning is based on the idea that in this case the comparative aspects of particular banks activity are taken into account, and also it's possible to obtain statistic ratings of significance and reliability of the results of the analysis made.…”
Section: Technical Efficiency As One Of the Valuables Of Bank Lendingmentioning
confidence: 99%
“…As the analysis literature sources shows [12]- [14], most studies of efficiency in the field of banking activity are based on usage of industrial approach, operational approach or an intermediary approach, which is based on the expenditure approach. Nevertheless, a bank is first of all a financial intermediary between the potential owners of spare money resources and different subjects of market relations who need such resources.…”
Section: Technical Efficiency As One Of the Valuables Of Bank Lendingmentioning
confidence: 99%